2019
DOI: 10.37358/mp.19.3.5216
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study on the Locally Blast Loaded Polyurea Coated Steel Plates

Abstract: The damages and casualties inflicted by mine and IED attacks in security challenging areas generated a strong and quick response from nations all over the world. As a part of this response several national and private research facilities increased their efforts in identifying and implementing new ways or technologies to enable blast wave mitigation. The current paper aim to investigate the opportunity of using polyurea coated steel plates as a possible new blast mitigation approach, as suggested by several inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Structurally, solid rocket composite propellants are typically based on a heterogeneous combination of distinct compounds that serve as fuel, oxidizer, burn-rate modifiers, and binder [1,2]. Usually, the applicability of polyurethane or polyurea matrices lies in the field of thermal insulations, hydro-isolations, adhesives, and ballistic protection [3][4][5][6]. In the case of energetic materials, they have a dual purpose, as a binding agent and as an organic fuel [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, solid rocket composite propellants are typically based on a heterogeneous combination of distinct compounds that serve as fuel, oxidizer, burn-rate modifiers, and binder [1,2]. Usually, the applicability of polyurethane or polyurea matrices lies in the field of thermal insulations, hydro-isolations, adhesives, and ballistic protection [3][4][5][6]. In the case of energetic materials, they have a dual purpose, as a binding agent and as an organic fuel [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, there was shown the importance of polymers in various military protection applications [1][2][3][4], and was demonstrated that the reinforcement of such polymers conducts to better composite materials, which possess higher strength and higher modulus [2,[5][6][7][8][9][10], in order to, e.g., reduce blunt trauma [10].…”
Section: Introductionmentioning
confidence: 99%
“…During high-velocity impacts, characterised in the range of 300–2500 ms −1 [ 16 , 17 ], the event is so short that the structure has no time to respond in global flexural or shear modes and so damage tends to be localised, taking the form of target penetration. During low-velocity impacts (generally regarded to be at velocities less than 10 ms −1 ), the impactor contact time is long enough for the entire FRP structure to respond to the impact [ 18 ].…”
Section: Introductionmentioning
confidence: 99%